Sistem Pendukung Keputusan Pemilihan Bidan Terbaik Dengan Metode MOORA (Studi Kasus: Rumah Sakit Ridos) - Dennita Pasaribu; Rivalri Kristianto Hondro (STMIK Budi Darma, 2019)
The aim of the Best Midwife is to find a midwife who is truly responsible for serving patients in a hospital or carrying out their duties in accordance with the legislation. The selection of the best midwife has a problem, namely the best bida selection system that is still manual as long as it is selected in the collection file to apply as a midwife in a hospital. So that the chosen midwife is not in accordance with what is expected, both in terms of ability, responsibility or others. To overcome this, a decision support system is needed using the MOORA method (Multi Object Optimization On The Base Of Ratio Analysis) that can help General Ridos Hospital in the selection of the Best Midwives.